2012
DOI: 10.1186/1471-2458-12-635
|View full text |Cite
|
Sign up to set email alerts
|

“Don’t wait for them to come to you, you go to them”. A qualitative study of recruitment approaches in community based walking programmes in the UK

Abstract: BackgroundThis study aimed to examine the experiences of walking promotion professionals on the range and effectiveness of recruitment strategies used within community based walking programmes within the United Kingdom.MethodsTwo researchers recruited and conducted semi-structured interviews with managers and project co-ordinators of community based walking programmes, across the UK, using a purposive sampling frame. Twenty eight interviews were conducted, with community projects targeting participants by age,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 19 publications
7
25
0
Order By: Relevance
“…The previous quote appeared to reflect previous findings that membership of walking groups is primarily by professionals who tend to further recruit from the retired, middle classes and women (Matthews et al., 2012). Recruitment of walkers by ‘word of mouth’ was a key recruitment strategy outlined in the bid document and it was envisaged that the Walking Champions would promote the scheme and, ‘spread the word’ to enable the recruitment of walkers into the scheme (SH5: Int.1).…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…The previous quote appeared to reflect previous findings that membership of walking groups is primarily by professionals who tend to further recruit from the retired, middle classes and women (Matthews et al., 2012). Recruitment of walkers by ‘word of mouth’ was a key recruitment strategy outlined in the bid document and it was envisaged that the Walking Champions would promote the scheme and, ‘spread the word’ to enable the recruitment of walkers into the scheme (SH5: Int.1).…”
Section: Resultssupporting
confidence: 70%
“…This is despite evidence that an in-depth understanding of a target group's perspective and involvement in ‘bottom-up’ planning is important in disadvantaged communities (Cleland et al., 2014). Additionally, active recruitment methods (those initiated by the programme) rather than passive (potential participant makes the first contact with the programme), such as ‘word of mouth’ are most effective in engaging hard to reach groups (Matthews et al., 2012). In fact, ‘word of mouth’ is likely to have the potential to increase inequity in walking group membership by utilising social networks that are restricted to the socially well connected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As has been noted in other studies, relationships with PCPs, administrators and staff at the health centers were key in recruiting participants [30] and maintaining high levels of retention. Nicholson et al (2011) found that administrative support in the form of desk space, access to patient schedules and medical records, and coordination with PCPs and nurses was important for participant retention [31].…”
Section: Discussionmentioning
confidence: 93%
“…5,6 Community-based health-promotion programs provide an opportunity to target health behaviours in the wider population and promote increases in fruit and vegetable intakes as well as an increase in physical activity across the population. [7][8][9] However, two components that are critical for their success, but are often overlooked, are effective recruitment and retention of participants.…”
Section: Introductionmentioning
confidence: 99%